Medicinal plants' proposed nanocomposites for the management of endocrine disorders. Issue 9 (September 2022) - Al Zarzour, Raghdaa Hamdan; Kamarulzaman, Ezatul Ezleen; Saqallah, Fadi G.; Zakaria, Fauziahanim; Asif, Muhammad; Abdul Razak, Khairul Niza
Abstract: Extensive attention has been focused on herbal medicine for the treatment of different endocrine disorders. In fact, compelling scientific evidence indicates that natural compounds might act as endocrine modulators by mimicking, stimulating, or inhibiting the actions of different hormones, such as thyroid, sex, steroidal, and glucose regulating hormones. These potentials might be effectively employed for therapeutic purposes related to the endocrine system as novel complementary choices. Nevertheless, despite the remarkable therapeutic effects, inadequate targeting efficiency and low aqueous solubility of the bioactive components are still essential challenges in their clinical accreditation. On the other hand, nanotechnology has pushed the wheels of combining inorganic nanoparticles with biological structures of medicinal bioactive compounds as one of the utmost exciting fields of research. Nanoparticle conjugations create an inclusive array of applications that provide greater compliance, higher bioavailability, and lower dosage. This can safeguard the global availability of these wealthy natural sources, regardless of their biological occurrence. This review inspects future challenges of medicinal plants in various endocrine disorders for safe and alternative treatments with examples of their nanoparticle formulations. Graphical abstract: Abstract : Endocrine disorders; Diabetes mellitus; Steroidal effects; Thyroid; Nanoparticles; Medicinal plants.